Risk-Based Intensive Blood Pressure Lowering and Prevention of Heart Failure: A SPRINT Post Hoc Analysis. Issue 6 (1st November 2021) - Molsberry, Rebecca J.; Rethy, Leah; Wang, Michael C.; Mehta, Rupal C.; Lloyd-Jones, Donald M.; Ning, Hongyan; Lewis, Cora E.; Yancy, Clyde W.; Shah, Sanjiv J.; Khan, Sadiya S.
Abstract : Supplemental Digital Content is available in the text. Abstract : The SPRINT (Systolic Blood Pressure Intervention Trial) demonstrated that intensive blood pressure (BP) lowering (target<120 mm Hg) was more effective in preventing heart failure (HF) compared with standard BP goals (target<140 mm Hg). However, intensive BP lowering also led to an increase in serious adverse events. We aimed to identify a subset of the clinical trial population who might derive the greatest benefit from intensive BP lowering for prevention of HF using a previously validated HF risk prediction model. SPRINT participants without prevalent cardiovascular disease were stratified into HF risk tertiles based on predicted HF risk. We performed Kaplan-Meier Survival analysis and multivariable Cox proportional hazards models to test the effect of intensive versus standard BP lowering on incident HF in each tertile of predicted HF risk. A total of 6911 individuals were included and 77 incident HF events occurred over a median follow-up time of 3.3 (interquartile range, 2.9–3.8) years. A reduction in risk of HF was observed among those randomized to intensive BP lowering in each risk tertile but was significant only in the highest HF risk category (risk tertile 1: hazard ratio, 0.86 [95% CI, 0.29–2.56]; risk tertile 2: 0.54 [0.23–1.30]; risk tertile 3: 0.46 [0.24–0.88]). Serious adverse events were frequent in all groups. While the short follow-up may lead to an underestimation of benefit in the lower predicted risk groups, prioritizing intensive BP lowering in those at highest predicted HF risk may help to reduce the high burden of HF in the United States.